Altered Neuronal Response During Rapid Auditory Processing and Its Relation to Phonological Processing in Prereading Children at Familial Risk for Dyslexia. (18th April 2013) - Raschle, Nora M.; Stering, Patrice L.; Meissner, Sarah N.; Gaab, Nadine
Abstract : Developmental dyslexia (DD) is a learning disability affecting 5–17% of children. Although researchers agree that DD is characterized by deficient phonological processing (PP), its cause is debated. It has been suggested that altered rapid auditory processing (RAP) may lead to deficient PP in DD and studies have shown deficient RAP in individuals with DD. Functional neuroimaging (fMRI) studies have implicated hypoactivations in left prefrontal brain regions during RAP in individuals with DD. When and how these neuronal alterations evolve remains unknown. In this article, we investigate functional networks during RAP in 28 children with ( n = 14) and without ( n = 14) a familial risk for DD before reading onset (mean: 5.6 years). Results reveal functional alterations in left-hemispheric prefrontal regions during RAP in prereading children at risk for DD, similar to findings in individuals with DD. Furthermore, activation during RAP in left prefrontal regions positively correlates with prereading measures of PP and with neuronal activation during PP in posterior dorsal and ventral brain areas. Our results suggest that neuronal differences during RAP predate reading instruction and thus are not due to experience-dependent brain changes resulting from DD itself and that there is a functional relationship between neuronal networks for RAP and PP within the prereading brain.